Evolutionary programming technique used for loss minimization in distribution system / Mohamad Azmil Nor Azaman - Nor Azaman, Mohamad Azmil (2014)
Network reconfiguration refers to the closing or opening of tie line switches and sectionalizing switches respectively in a power network to alter the topological structure of the distribution feeder. By changing the topology, minimum power losses can be achieved. A common optimization technique called Evolutionary Programming (EP) has been chosen. For the purpose of this research, the IEEE 69-bus system was used to analyze the viability and performance of the EP technique. The EP is expected to have convergence value which cause the result to be optimum and at the same time minimize the power losses in the 69-bus system.